Unilateral Nasal Obstruction during Later Growth Periods Affects Craniofacial Muscles in Rats - Uchima Koecklin, Karin H.; Hiranuma, Maya; Kato, Chiho; Funaki, Yukiha; Kataguchi, Taku; Yabushita, Tadachika; Kokai, Satoshi; Ono, Takashi (Frontiers in Physiology, 2017)
Nasal obstruction can occur at different life stages. In early stages of life the respiratory system is still under development, maturing during the growth period. Previous studies have shown that nasal obstruction in neonatal rats alters craniofacial function. However, little is known about the effects of nasal obstruction that develops during later growth periods. The aim of this study was to investigate the effects of nasal obstruction during later periods of growth on the functional characteristics of the jaw-opening reflex (JOR) and tongue-protruding muscles. In total, 102 6-day-old male Wistar rats were randomized into either a control or experimental group (both n = 51). In order to determine the appropriate timing of nasal obstruction, the saturation of arterial oxygen (SpO2) was monitored at 8 days, and at 3, 5, 7, 9, and 11 weeks in the control group. Rats in the experimental group underwent unilateral nasal obstruction at the age of 5 weeks. The SpO2 was monitored at 7, 9, and 11 weeks in the experimental group. The electromyographic responses of JOR and the contractile properties of the tongue-protruding muscles were recorded at 7, 9, and 11 weeks. In the control group, SpO2 decreased until 5 weeks of age, and remained relatively stable until 11 weeks of age. The SpO2 was significantly lower in the experimental group than in the control. In the experimental group, JOR changes included a longer latency and smaller peak-to-peak amplitude, while changes in the contractile properties of the tongue-protruding muscles included larger twitch and tetanic forces, and a longer half-decay time. These results suggest that nasal obstruction during later growth periods may affect craniofacial function.